Identifikasi Litologi dan Pergerakan Tanah Menggunakan Metode Mikrotremor Wilayah Barat di Desa Kalongan, Kecamatan Ungaran Timur, Kabupaten Semarang Jawa Tengah - Indah Enggar Pratiwi; Handayani, Wuri (Jurnal Stasiun Geofisika Sleman, 2024)
Landslides or often called land movements have occurred in Kalongan Village, East Ungaran District, Semarang Regency. This research uses the microtremor method for the purpose of determining the dominant frequency (f0), amplification (A0), seismic vulnerability index (Kg), and subsurface lithology analysis based on shear wave velocity (Vs) values in Kalongan Village, East Ungaran District. In the area to be analyzed (to the west) there are two formations, namely the Kerek Formation and the Kaligetas Formation. The research results provide information about areas in Kalongan Village that have seismic vulnerability values (Kg) which have the potential to experience damage if ground movement occurs, such as at the KL 59 location which has soft soil with sedimentary rock lithology which is very vulnerable to earthquakes. The lithology of Kalongan Village as a whole consists of layers of Tuffan Sandstone, interbedded Claystone, Conglomerate in the Kerek Formation and Volcanic Breccia in the Kaligetas Formation.